Peran Guru Kelas Dalam Pelaksanaan Bimbingan Konseling Di Sekolah Inklusi Sd Al Firdaus Surakarta - Dwi Pamuji, Rowi, Drs. Saring Marsudi, SH. M.Pd (2017)
This study aims to: 1) Criteria of students who receive counseling treatment in Elementary School Inclusive Education of Al Firdaus Surakarta. 2) Implementation of counseling that conducted by classroom teachers on inclusive education elementary school Al Firdaus Surakarta. 3) Knowing the obstacles and solutions in the implementation of counseling guidance on inclusive education Elementary School Al Firdaus Surakarta. This research is a qualitative research with qualitative descriptive design. The informants of the research are principal, teachers grade 2 and 5, teacher assistants, and students. Data collection techniques which is used is observation, interview, and documentation. The validity of research data uses triangulation of sources and methods. The results showed that the class teacher's role in the implementation of counseling guidance on inclusive education is very important because must understand criteria of student, obstacles and solutions in implementing the counseling guidance. Implementation of counseling guidance on inclusive education should be structured and programmed. Criteria of students who obtain counseling guidance consists of various kinds of both children with disabilities and general children, such as conducting disorder and violating rules or regulations in school. Obstacle's classroom teacher in implementing counseling guidance such as lack of approaches and methods, as well as the experience of classroom teachers is low. Solutions for classroom teachers to solve the problem is dealing with cooperation to outside parties who are bound as teacher assistant, psychologist or counselor, inclusion'team, and parents.